Adherence evaluation of vented chest seals in a swine skin model. Issue 10 (October 2016) - Arnaud, Françoise; Maudlin-Jeronimo, Eric; Higgins, Adam; Kheirabadi, Bijan; McCarron, Richard; Kennedy, Daniel; Housler, Greggory
Abstract: Objectives: Perforation of the chest (open pneumothorax) with and without lung injury can cause air accumulation in the chest, positive intrapleural pressure and lead to tension pneumothorax if untreated. The performance of chest seals to prevent tension physiology depends partially on their ability to adhere to the skin and seal the chest wound. Novel non-occlusive vented chest seals were assessed for their adhesiveness on skin of live swine under normal and extreme environmental conditions to simulate austere battlefield conditions. Methods: Chest seals were applied on the back of the swine on skin that was soiled by various environmental contaminants to represent battlefield situations. A peeling (horizontal rim peeling) and detachment and breaching (vertical pulling) techniques were used to quantify the adhesive performance of vented chest seals. Among eight initially selected vented seals, five (Bolin, Russell, Fast breathe, Hyfin and SAM) were further down-selected based on their superior adherence scores at ambient temperatures. The adherence of these seals was then assessed after approximately 17 h storage at extreme cold (−19.5 °C) and hot (71.5 °C) temperatures. Results: Adherence scores for peeling (above 90%) and detachment scores (less than 25%) were comparable for four vented chest seals when tested at ambient temperature, except for the Bolin seal which had higher breaching. Under extreme storage temperatures, adherence peeling scores were comparable to those at ambient temperatures for four chest seals. Scores were significantly lower for the Bolin seal at extreme temperatures. This seal also had the highest detachment and breaching scores. In contrast, the Russell, Fast breathe, Hyfin and SAM seals showed similar ability to stay air tight without breaching after hot storage. Conclusion: No significant difference was found in skin adherence of the five vented chest seals at ambient temperature and the four seals (Russell, Fast breathe, Hyfin and SAM) maintained superior adherence even after exposure to extreme temperatures compared to the Bolin. To select the most effective product from the 5 selected vented chest seals, further functional evaluation of the valve of these chest seals on a chest wound with the potential for tension in the pneumothorax or hemopneumothorax is warranted.